Evaluasi Galur Haploid Ganda Pelestari Hasil Kultur Antera untuk Perakitan Galur Mandul Jantan pada Padi - Indrastuti A. Rumanti; Iswari S. Dewi; Bambang S. Purwoko; Hajrial Aswidinnoor (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Hybrid rice has been proven to be the key factor to increase food supply in highly populated countries such as China and India. The success has encouraged the government of Indonesia to intensify research and development on hybrid rice using cytoplasmic-genetic male sterility system. The use of good male sterile line is a prerequisite for commercial seed production of hybrid rice.  The objective of this research was to evaluate several F1 plants to develop completely sterile cytoplasmic male sterile line (CMS) with good agronomic characters.  This research was conducted at screen house of Bogor Agricultural University during dry season (DS) of 2007.  Fourty eight F1s, derived from testcross between cytoplasmic male sterile sources with doubled-haploid (DH) maintainer lines, were evaluated in randomized complete design using three replications.  Observation was done on pollen sterility, panicle and stigma exsertion, plant height, and tillering ability.  The results showed 14 F1s were completely sterile (100 % pollen sterility).  They were A-2/H36-3-Ma, A-1/H36-3-Mb, A-2/H36-3-Mb, A-3/H36-3-Mb, A-1/H36-4-M, A-2/B1-1-Mb, A-3/B1-1-Mb, A-1/B1-2-Pa, A-2/B1-2-Pb, A-3/B2-1-M, A-1/B2-4-Pb, A-3/B4-1-Da, A-1/B4-1-Dc, and A-3/B4-1-Dc.  They also had early flowering date, averaged from 66 - 90 days after planting (DAP).  There were other 14 F1s with stigma exsertion more than 70 % and good panicle exsertion, i.e.  A-2/H36-3-Mb, A-1/H36-3-Mc, A-2/H36-3-Mc, A-1/H36-4-M, A-2/B1-2-Pa, A-2/B1-2-Pb, A-3/B2-1-Db, A-1/B2-1-Dc, A-1/B2-1-M, A-1/B2-4-Pb, A-3/B2-4-Pb, A-2/B4-1-Da, A-1/B4-1-Dc and A-3/B4-1-Dc.  However, only five F1s had all desirable characteristics as male sterile line candidates, such as 100% pollen sterility, good panicle exsertion, high stigma exsertion, semi-dwarf in plant height and good tillering ability.  They were A-1/H36-4-M, A-2/B1-2-Pb, A-1/B2-4-Pb, A-1/B4-1-Dc, A-3/B4-1-Dc.   Key words:  Doubled-haploid maintainer lines, CMS, pollen sterility, hybrid rice